Effect of a combination of whole body vibration exercise and squat training on body balance, muscle power, and walking ability in the elderly - Osugi T; Iwamoto J; Yamazaki M; Takakuwa M (Dove Medical Press, 2014)
Tomohiro Osugi,1 Jun Iwamoto,2 Michio Yamazaki,1 Masayuki Takakuwa3 1Department of Rehabilitation, Takakuwa Orthopaedic Nagayama Clinic, Asahikawa, Hokkaido, 2Institute for Integrated Sports Medicine, Keio University School of Medicine, Shinjuku-ku, Tokyo, 3Department of Orthopaedic Surgery, Takakuwa Orthopaedic Nagayama Clinic, Asahikawa, Hokkaido, Japan Abstract: A randomized controlled trial was conducted to clarify the beneficial effect of whole body vibration (WBV) exercise plus squat training on body balance, muscle power, and walking ability in the elderly with knee osteoarthritis and/or spondylosis. Of 35 ambulatory patients (14 men and 21 women) who were recruited at our outpatient clinic, 28 (80.0%, 12 men and 16 women) participated in the trial. The subjects (mean age 72.4 years) were randomly divided into two groups (n=14 in each group), ie, a WBV exercise alone group and a WBV exercise plus squat training group. A 4-minute WBV exercise (frequency 20 Hz) was performed 2 days per week in both groups; squat training (20 times per minute) was added during the 4-minute WBV training session in the WBV exercise plus squat training group. The duration of the trial was 6 months. The exercise and training program was safe and well tolerated. WBV exercise alone improved indices of body balance and walking velocity from baseline values. However, WBV exercise plus squat training was more effective for improving tandem gait step number and chair-rising time compared with WBV exercise alone. These results suggest the benefit and safety of WBV exercise plus squat training for improving physical function in terms of body balance and muscle power in the elderly. Keywords: whole body vibration exercise, squat training, body balance, walking velocity, muscle power